Gender, Social Inequalities and Application of Climate Smart Agriculture Practices among Smallholder Farmers in Ghana - Kofituo, Rich Kofi; Dalaa, Mustapha Alasan; Tepa-Yotto, Ghislain; Adomaa, Faustina Obeng; Mponela, Powell; Odoi, Maureen Erekua; Tahidu, Osman Damba (International Institute of Tropical Agriculture, 2023)
Farmers in Ghana have suffered from the effects of climate change. These negative effects are more severe among women and youth farming groups. Research in Ghana has been focused on developing climate-smart agriculture (CSA) practices to mitigate the negative effect of climate change on farmers productivity. The study uses baseline data from the Accelerating impacts of CGIAR climate research for Africa (AICCRA) project to analyze social inequalities and gender dimensions in the application of CSA practices among maize, cowpea, yam, sweet potato and tomato farmers in Ghana. A total of 551 farmers (≃30% female) were interviewed in six regions using an exploratory research design approach. All farmers practice at least one of the CSA practices, that is use of disease- and pest-tolerant varieties, minimum tillage, ridging, mulching, promotion of stress- tolerant improved varieties, composting, organic amendment for improving soil health, planting of Mucuna pruriens and organic amendment. Further findings show that male farmers are more resource rich in all regions of the study, apart from the Bono East Region. In terms of agricultural land holdings, male farmers own more lands than female farmers. Female farmers have more access to climate information in Bono East, Central and Upper East regions. Overall, male farmers have more access to credit than female farmers. From a policy perspective, in order to enhance equitable application of CSA practices among farmers, stakeholders must operationalize laws guiding tenure of farm lands, and there must be effective climate information dissemination coupled with facilitation of agricultural credit and loan facility to mostly female farmers.